AN ANALYSIS OF INNOVATION AND CULTURAL DIVERSITY IN THE CHALLENGES AND PERSPECTIVES OF LOCAL COMPANIES' DEVELOPMENT: AN EXAMPLE OF AZERBAIJAN - JABRAYILOV, Mahammad (Annals of Spiru Haret University. Economic Series, 2019)
The role of innovation is crucial for countries and businesses to gain competitive advantage. The key to success in the competitive process is to have a culture of innovation. The purpose of this study is to identify the link between innovation and cultural diversity in company management, which is one of the most important sources of competitive advantage, and to explore the role they play in company management. In this regards, a comprehensive review of innovation, cultural diversity and organizational culture has been conducted and links are established. The study concludes that innovation and cultural diversity have a major impact on innovation in companies and services. This study seeks to provide a comprehensive overview of the role of local innovation companies in the development challenges and perspectives, while providing insights into the concepts of innovation and cultural diversity. Research work can be considered as a good source for experts, researchers, and scientists working in this field.